SIKAP KONSUMEN TERHADAP CITRA TOKO DISTRO INSPIRED DI KOTA MALANG - Karnawati, Tin Agustina (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: This study aimed to know the attitude of consumers at the store image which includes product, service, atmosphere and store promotions distribution outlets Inspired in the city of Malang, Results showed  that positive  attitude of consumers on the image of the product, service, atmosphere and store promotions give a good description of the assessment on the distribution outlets Inspired Malang, whereas consumers of social environment to form a subjective norm in influencing consumers to visit distribution outlets Inspired in Malang is positive too, so that can concluded that the attitude of consumers and subjective norm together determine the intent of consumer behavior positively to the distribution outlets Inspired Malang. Ke ywords: consumer attitudes, subjective norms, behavioral intentions of consumers,   and distribution outlets image.